2014
DOI: 10.1038/nature13560
|View full text |Cite
|
Sign up to set email alerts
|

A shift of thermokarst lakes from carbon sources to sinks during the Holocene epoch

Abstract: Thermokarst lakes formed across vast regions of Siberia and Alaska during the last deglaciation and are thought to be a net source of atmospheric methane and carbon dioxide during the Holocene epoch. However, the same thermokarst lakes can also sequester carbon, and it remains uncertain whether carbon uptake by thermokarst lakes can offset their greenhouse gas emissions. Here we use field observations of Siberian permafrost exposures, radiocarbon dating and spatial analyses to quantify Holocene carbon stocks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
345
3
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(366 citation statements)
references
References 53 publications
17
345
3
1
Order By: Relevance
“…Their lifetime e in contrast to the onset e largely depends on local factors such as geomorphology, ground-ice conditions, hydrology and groundsurface stability (Jones et al, 2011(Jones et al, , 2012Jones and Arp, 2015). The initiation of many thermokarst lakes in northwest Canada, Alaska, and Siberia is related to increasing air temperatures, available moisture and permafrost thaw in response to short-term warming events during the Pleistocene-Holocene transition or later on during the Holocene thermal maximum (Rampton, 1988;Brosius et al, 2012;Walter Anthony et al, 2014). However, Burn and Smith (1990) noted that such lakes may also develop in response to site-specific factors such as ground disturbance, which are not necessarily related to regional climatic change.…”
Section: Thermokarst and Thaw Lake Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their lifetime e in contrast to the onset e largely depends on local factors such as geomorphology, ground-ice conditions, hydrology and groundsurface stability (Jones et al, 2011(Jones et al, , 2012Jones and Arp, 2015). The initiation of many thermokarst lakes in northwest Canada, Alaska, and Siberia is related to increasing air temperatures, available moisture and permafrost thaw in response to short-term warming events during the Pleistocene-Holocene transition or later on during the Holocene thermal maximum (Rampton, 1988;Brosius et al, 2012;Walter Anthony et al, 2014). However, Burn and Smith (1990) noted that such lakes may also develop in response to site-specific factors such as ground disturbance, which are not necessarily related to regional climatic change.…”
Section: Thermokarst and Thaw Lake Dynamicsmentioning
confidence: 99%
“…As the terrestrial Arctic warms up, permafrost soils, including those located in IWPs in drained lake basins, are expected to release substantial greenhouse gas emissions that will generate a positive feedback to global warming (Dutta et al, 2006;Koven et al, 2011;Schaefer et al, 2014). Walter Anthony et al (2014) indicated that widespread permafrost thaw could ultimately result in reduced lake and wetland abundance caused by drainage and drying, facilitating rapid decomposition of freeze-locked organic matter. Yet, these estimations were based on sampling performed on thermokarst basins in permafrost environments of the Yedoma region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lakes can also emit a substantial amount of CO 2 (Kling et al, 1991;Cole et al, 1994;Algesten et al, 2004). Although lakes are large CH 4 and CO 2 sources, they also have the potential to sequester carbon as lake sediments and peat accumulate with time ( Jones et al, 2012;Walter-Anthony et al, 2014).…”
Section: Figure 10mentioning
confidence: 99%
“…The latter brings about a shorter residence time of lakes, whose size changes, especially at southern latitudes, due to the disappearance of sporadic and isolated permafrost. It is also worth noting the primary role of lakes in controlling greenhouse gas exchange with the atmosphere, both in permafrost-free [21,22] and permafrost-bearing regions [9,[23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%